Allium pseudotelmatum (Amaryllidaceae), a new species of Allium sect. Codonoprasum from Croatia - Jandová, Michaela; Oulehlová, Martina; Vojtěchová, Kateřina; Kitner, Miloslav; Duchoslav, Martin (Phytotaxa, 2017)
Allium pseudotelmatum, a new species of A. sect. Codonoprasum, is described from the southern Dalmatia (Croatia). It is a late-summer flowering species with pentaploid (2n = 40) chromosome complement, occurring in synanthropic habitats (Citrus orchards with nutrient rich and fresh moist soil). Karyology, leaf anatomy, morphology, ecology, molecular (ITS) and taxonomic relationships with related species are examined for the species. It shows morphological relationships with the northern Dalmatian species A. telmatum from which it well differentiates for many morphological characters including the presence of aerial bulbils within the inflorescence, phenology, chromosome number and ecology. Confusion of A. pseudotelmatum with some specimens of A. oleraceum due to the presence of bulbils within the inflorescence is discussed.